a, x^2 - x - 20 = 0
=> x^2 - 5x + 4x - 20 = 0
=> x(x - 5) + 4(x - 5) = 0
=> (x + 4)(x - 5) = 0
=> x + 4 = 0 hoặc x - 5 = 0
=> x = -4 hoặc x = 5
b, x^3 - 6x^2 + 12x + 19 = 0
=> x^3 + x^2 - 7x^2 - 7x + 19x + 19 = 0
=> x^2(x + 1) - 7x(x + 1) + 19(x + 1) = 0
=> (x^2 - 7x + 19)(x + 1) = 0
x^2 - 7x + 19 > 0
=> x + 1 = 0
=> x = -1
\(a,x^2-x-20=0\)
\(x^2-5x+4x-20=0\)
\(\left(x-5\right)\left(x-4\right)=0\)
\(\orbr{\begin{cases}x-5=0\\x-4=0\end{cases}\Rightarrow\orbr{\begin{cases}x=5\\x=4\end{cases}}}\)
\(b,x^3-6x^2+12x+19=0\)
\(\left(x^3+x^2\right)-\left(7x^2+7x\right)+\left(19x+19\right)=0\)
\(\left(x+1\right)\left(x^2-7x+19\right)=0\)
Vì \(\left(x^2-7x+19\right)>0\forall x\)
\(x+1=0\)
\(x=-1\)
\(x^2-x-20=0\)
\(\Leftrightarrow x^2-5x+4x-20=0\)
\(\Leftrightarrow x\left(x-5\right)+4\left(x-5\right)=0\)
\(\Leftrightarrow\left(x-5\right)\left(x+4\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x-5=0\\x+4=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=5\\x=-4\end{cases}}}\)
\(x^3-6x^2+12x+19=0\)
\(\Leftrightarrow x^3+x^2-7x^2-7x+19x+19=0\)
\(\Leftrightarrow x^2\left(x+1\right)-7x\left(x+1\right)+19\left(x+1\right)=0\)
\(\Leftrightarrow\left(x+1\right)\left(x^2-7x+19\right)=0\)
Ta có: \(x^2-7x+19>0\forall x\)
\(\Rightarrow x+1=0\)
\(\Leftrightarrow x=-1\)
Vậy x=-1